In silico studies and in vitro evaluation of isatin-pyridine oxime hybrids as novel reactivators of acetylcholinesterase inhibited by an A-230 surrogate - Bernardo, Leandro B; Vieira, Leandro A; Borges, Caio V N; Buitrago, Pedro A G; Kuča, Kamil; França, Tanos C C; Cavalcante, Samir F A; Sousa, Roberto B; Lima, Antônio L S; Kitagawa, Daniel A S (Archives of toxicology, 2025)
Recent events involving nerve agents of the A-Series, a once elusive class of chemical warfare agents, have provoked a great concern in the international community. In this paper, continuing our research efforts in Medicinal Chemistry at the Brazilian Institute of Chemical, Biological, Radiological and Nuclear Defense (IDQBRN) (an OPCW-designated Laboratory for environmental samples), we explore ANMP, an A-230 surrogate, in the search for new treatment options for intoxications caused by these chemicals. Five isatin-pyridine oxime hybrids were evaluated as acetylcholinesterase (AChE) reactivators using a modified Ellman's assay. Our results indicate that monocationic hybrids with five methylene units, as well as its oxa-analog, are promising compounds for the design of new AChE reactivators.
Keywords: Acetylcholinesterase; Cholinesterase Reactivators; cholinesterasové inhibitory; acetylcholinesterasa; Isatin; Computer Simulation; počítačová simulace; Cholinesterase Inhibitors; Pyridines; pyridiny; Chemical Weapons Convention; Oximes; isatin; Nerve agents; vztahy mezi strukturou a aktivitou; chemické bojové látky; Antidotes; Chemical Warfare Agents; Isatin hybrids; Structure-Activity Relationship; oximy; reaktivátory cholinesterasy